Extracellular Prion Protein Aggregates in Nine Gerstmann–Sträussler–Scheinker Syndrome Subjects with Mutation P102L: A Micromorphological Study and Comparison with Literature Data - Jankovska, Nikol; Matej, Radoslav; Olejar, Tomas (International journal of molecular sciences, 2021)
Gerstmann–Sträussler–Scheinker syndrome (GSS) is a hereditary neurodegenerative disease characterized by extracellular aggregations of pathological prion protein (PrP) forming characteristic plaques. Our study aimed to evaluate the micromorphology and protein composition of these plaques in relation to age, disease duration, and co-expression of other pathogenic proteins related to other neurodegenerations. Hippocampal regions of nine clinically, neuropathologically, and genetically confirmed GSS subjects were investigated using immunohistochemistry and multichannel confocal fluorescent microscopy. Most pathognomic prion protein plaques were small (2–10 µm), condensed, globous, and did not contain any of the other investigated proteinaceous components, particularly dystrophic neurites. Equally rare (in two cases out of nine) were plaques over 50 µm having predominantly fibrillar structure and exhibit the presence of dystrophic neuritic structures; in one case, the plaques also included bulbous dystrophic neurites. Co-expression with hyperphosphorylated protein tau protein or amyloid beta-peptide (Aβ) in GSS PrP plaques is generally a rare observation, even in cases with comorbid neuropathology. The dominant picture of the GSS brain is small, condensed plaques, often multicentric, while presence of dystrophic neuritic changes accumulating hyperphosphorylated protein tau or Aβ in the PrP plaques are rare and, thus, their presence probably constitutes a trivial observation without any relationship to GSS development and progression.